Synthesis And Characterization Of Coal2o4 And Co-Al2O3-Coal2o4 Catalysts Activity In Carbon Dioxide Reforming Of Methane - Wong, Yee Jie (2016)
The production of syngas (hydrogen, H2 and carbon monoxide, CO) through carbon dioxide reforming of methane (CRM) is a promising process that simultaneously utilizes two greenhouse gases, i.e., methane, CH4 and carbon dioxide, CO2. Currently, the use of biogas as a cheap feedstock for CRM is very alluring due to the its nearly 1:1 ratio of CH4 and CO2 content, which is ideal for this reaction. However, a catalyst made of earth-abundant elements and highly active in CRM is still in demand thus was made a subject of investigation in this project. In this study, the activity of Co(x)Al(3-x)O4 and Co-Al2O3-CoAl2O4 catalysts were investigated. The amount of cobalt, Co content in the catalyst were altered and denoted as x%-Co, where x range from 11.11% to 42.83%. Co(x)Al(3-x)O4 were prepared by sol-gel method at different Co and Al loading while Co-Al2O3-CoAl2O4 were prepared by reducing the freshly synthesized x%-Co compound with H2. 33.33%-Co was the best performing catalyst which produced 90.37% and 96.02% yield for H2 and CO, respectively at 900 °C, weight hourly space velocity (WHSV) of 15000 mlg-1h-1 and CH4 to CO2 feed ratio of 1:1. There was no observable catalytic activity decay within 24 h of reaction time and the rate of carbon deposition was at 3.1×10-2 g·gcat -1 ·h-1. Reduced 33.33%-Co was able to produces CH4 and CO2 conversion of 72.89 % and 79.49 %, respectively at 750 °C with a carbon formation rate of 1.7×10-2 g·gcat -1h-1. Study on the effect of Co content on reduced x%-Co in CRM reaction revealed that 15.79%-Co was able to achieve a constant conversion of 67.39 % and 78.54 % for CH4 and CO2, respectively at the reaction temperature of 750 °C, WHSV of 30000 mlg-1h-1 and CH4 to CO2 feed ratio of 1:1 for 50 h with rate of carbon deposition at 4.26×10-4 g·gcat -1·h-1.